Identification of a Plant Growth Promoting Rhizobacteria, Bacillus Sphaericus (UPMB10), Using PCR-Based DNA Fingerprinting Technique - Khor, Sock kun (2002)
One of the major constraints in increasing crop yield is the supply of nutrient and nitrogen is obviously the main limiting nutrient. Biological nitrogen fixation is believed to have a great potential to contribute to productive and sustainable agricultural system for the tropics. Bacillus sphaericus UPMB10 is a locally isolated plant growth promoting rhizobacteria that has the ability to fix atmospheric nitrogen efficiently and has been proven to promote the growth of vegetable soybean, oil palm and bananas. When UPMB10 is applied to the soil as a biofertilizer, it is very important to have a method of identifying and monitoring the effectiveness of the introduced inoculant. Polymerase chain reaction based DNA fingerprinting, a DNA polymorphism assay based on the amplification of random DNA segment with single primers of arbitrary nucleotide sequence, was employed to detect UPMB10 used as an inoculant. DNA polymorphism simply detects DNA segments, which are amplified from one individual bacterium but not others and the polymorph isms function as genetic markers. peR amplification does not require the culturing of the bacterial strains and since it is capable of amplifying unique sequences in the midst of a myriad of DNA sequences, it has the potential to identify specific strains found within the soil. The objectives of this study were to identify suitable primers for identification and distinguishing UPMB1 0 when applied as a biofertilizer.